Baicalein Prevents 6-Hydroxydopamine-Induced Dopaminergic Dysfunction and Lipid Peroxidation in Mice - Heh-In Im; Wan Seok Joo; Eunjoo Nam; Eun-sun Lee; Yu-jin Hwang; Yong Sik Kim (Elsevier, 2005)
The effects of baicalein on 6-hydroxydopamine (6-OHDA)-induced neurotoxicity were evaluated. Intracerebroventricularly (i.c.v.) injection of 6-OHDA was done to young mice. Baicalein was administered intraperitoneally 30 min before and 90 min after i.c.v. injection. Animals received further injection of bacalein daily for 3 consecutive days. Rotarod performance was assessed, tyrosine hydroxylase (TH) Western blotting was performed, and dopamine (DA) levels and peroxidation were determined. High dose of baicalein effectively improved rotarod performance and prevented the reduction of striatal DA levels and TH contents in the striatum and subtantia nigra (SN). In addition, lipid peroxidation level was decreased by baicalein at 3 and 7 days after 6-OHDA injection. These results showed that baicalein effectively prevents the 6-OHDA-induced dopaminergic dysfunction through an antioxidative action. Keywords:: 6-hydroxydopamine, baicalein, tyrosine hydroxylase